THE AUTHORITY OF THE CONSTITUTIONAL COURT IN HANDLING CONSTITUTIONAL COMPLAINTS: A COMPARATIVE STUDY WITH GERMANY AND SOUTH KOREA: KEWENANGAN MAHKAMAH KONSTITUSI DALAM MENANGANI PENGADUAN KONSTITUSIONAL: STUDI KOMPARATIF DENGAN JERMAN DAN KOREA SELATAN - Desak Ayu Gangga Sitha Dewi; Xavier Nugraha; Melva Emely Laurentius (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
Until now, there is still no authority of the Constitutional Court to examine constitutional complaint cases, even though at least 30 (thirty) cases are declared unacceptable because the substance of the petition is constitutional complaint. In several countries, constitutional complaint has become one of the powers of the Constitutional Court as a legal remedy that citizens can take if there is a violation of their constitutional rights, such as in Germany and South Korea. Based on this background, the formulation of the problem in this is first, what is the urgency of adding constitutional complaint as the authority of the Constitutional Court of the Republic of Indonesia? Second, how is the legal construction of the implementation of constitutional complaint in Indonesia? This research is legal research with a statutory, conceptual, and comparative approach. This research will describe first, the urgency of adding constitutional complaint as the authority of the Constitutional Court of the Republic of Indonesia and second, the legal construction of the application of constitutional complaint in Indonesia by comparing the arrangement and implementation of constitutional complaint in other countries, namely Germany and South Korea.